Quovadis Kebijakan Study Tour Sekolah? : Sebuah Perbedaan Perspektif Antara Kebijakan Gubernur Jawa Barat dan Kementerian Pendidikan Dasar dan Menengah - Amir, Faizal; Muhamad Mujadid; Moh Saiful Bakhril Amin (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to analyze the policy dynamics behind the study tour ban issued by the Governor of West Java and compare it with the approach taken by the Ministry of Primary and Secondary Education. Using a qualitative-descriptive approach and grounded in several theoretical frameworks—including the Policy Cycle Theory, Multiple Streams Framework (MSF), Asymmetric Decentralization and Intergovernmental Relations (IGR), Contextual Teaching and Learning (CTL), Experiential Learning, Critical Theory in Education, and the Advocacy Coalition Framework (ACF)—this research finds that the policy divergence stems from differences in policy stages, central-local government dynamics, and conflicting values between pedagogical goals and social justice concerns. A survey of 62 respondents comprising teachers, school principals, retired educators, and education officials reveals that most support out-of-school learning activities, provided they are educational, affordable, safe, and inclusive. The findings suggest that a total ban on study tours contradicts the principles of contextual learning and character education. Therefore, a redefinition of study tours as structured educational visits is necessary, along with improved policy coordination between central and regional authorities to realize an equitable, relevant, and student-centered education policy.